New Cubic B-spline Approximation for Solving Non-linear Singular Boundary Value Problems Arising in Physiology - Iqbal, Muhammad Kashif; Abbas, Muhammad; Khalid, Nauman (Communications in Mathematics and Applications, 2018)
In this article, a new cubic B-spline approximation method is presented for solving second order singular boundary value problems. The proposed numerical technique is based on cubic B-spline collocation method equipped with a new approximation for second order derivative. Several test problems arising in the field of Physiological sciences are considered. The approximate results are compared with the numerical techniques existing in literature. It is found that our new approximation performs superior to current methods due to its simplicity, straight forward interpolation and less computational cost.